Price Structure And Network Externalities In The Telecommunications Industry : Evidence From Sub-Saharan Africa - Iimi, Atsushi (The World Bank, 2007)
Many developing countries have experienced significant developments in their telecommunications network. Countries in Africa are no exception to this. The paper examines what factor facilitates most network expansion using micro data from 45 fixed-line and mobile telephone operators in 18 African countries. In theory the telecommunications sector has two sector-specific characteristics: network externalities and discriminatory pricing. It finds that many telephone operators in the region use peak and off-peak prices and termination-based price discrimination, but are less likely to rely on strategic fee schedules such as tie-in arrangements. The estimated demand function based on a discreet consumer choice model indicates that termination-based discriminatory pricing can facilitate network expansion. It also shows that the implied price-cost margins are significantly high. Thus, price liberalization could be conducive to development of the telecommunications network led by the private sector. Some countries in Africa are still imposing certain price restrictions. But more important, it remains a policy issue how the authorities should ensure reciprocal access between operators at reasonable cost